Relación entre la respiración y la germinación con el contenido de humedad en las semillas de cacao - Casas P, I.A.; Ibañez, M.L. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Cacao seeds were dehydrated for 24, 48, 72 and 96 hours in order to lower their water content. Subsequent studies were carried out comparing respiration rate and percentage of germination of seeds with moisture content. The results indicated the respiration decreased as did percentage of water in the seed. When the moisture content dropped to 17 percent there was an abrupt lowering of the respiration rate which reached zero when water content reached 14 percent. Germination or seed viability remained 100 percent up to 25 percent of moisture but began decrease rapidly to zero by the time only time only 16 percent of the water remained. The close relation of viability and respiration at lower percentages of water content suggests that the role of water in cacao seeds is more critical than in seeds which possess a dormant phase. The relationship of these studies to the long term storage of cacao seeds is discussed.